Government Strategy in Efforts to Combat Radicalism and Terrorism in Indonesia - Suharna, Karmin; Mulyana, Yaya; Turmudzi, Didi (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2025)
This study aims to analyze the Indonesian government's strategy in countering radicalism and terrorism by highlighting inter-agency coordination, the effectiveness of counter-radicalization and deradicalization programs, and the influence of social, cultural, and economic factors on policy implementation. Qualitative methods were used through analysis of policy documents, focus group discussions (FGDs), and in-depth interviews with relevant stakeholders. The results indicate that although the government has designed comprehensive policies, coordination across institutions such as the Coordinating Ministry for Political, Legal, and Security Affairs, the National Counterterrorism Agency (BNPT), the Indonesian National Armed Forces (TNI), the Indonesian National Police (Polri), and related ministries still faces structural and communication barriers, resulting in incomplete integration of policies. Social factors such as intolerance, stigma against former perpetrators, and economic inequality also hinder the success of deradicalization programs. This study also emphasizes the crucial role of civil society, religious leaders, and the private sector in strengthening government strategies through economic empowerment, national education, and digital literacy. To increase the effectiveness of counter-radicalization efforts, it is recommended to strengthen multidisciplinary research, develop anti-radicalization education curricula, implement integrated training for officials, and utilize digital technology for early detection and counter-radicalization campaigns. A collaborative and community-based approach is key to the success of a sustainable and adaptive strategy that adapts to Indonesia's social dynamics.